Perancangan Aplikasi Pendataan Stok Opname Gudang Berbasis Web Menggunakan Metode Waterfall pada Kopiluvium - Yuniarti, Dian Tri; Alfitra, Ramadhani; Prasetya, Rivaldi Nicho; Saprudin (CV. Multi Kreasi Media, 2025)
This study discusses the design of a web-based stock opname recording application for Kopiluvium using the Waterfall method. The application is designed to address the challenges of manual stock recording, which is prone to errors, slow, and inefficient. The Waterfall method is implemented through the stages of requirements analysis, system design, implementation, testing, and maintenance. Tools used include PHP, MySQL, and UML diagrams (Use Case Diagram, Activity Diagram, ERD). The system includes multi-level login (admin, staff, employee), item data input, stock in/out recording, automatic reports, and role-based access. Testing using the blackbox method shows that the system functions according to user needs. This study demonstrates that a web-based system can improve warehouse stock recording efficiency and support faster, more accurate managerial decision-making.